PENGARUH KOMPLEKSITAS PERUSAHAAN, JENIS INDUSTRI, PROFITABILITAS KLIEN, UKURAN PERUSAHAAN DAN KOMISARIS INDEPENDEN TERHADAP FEE AUDIT - Salsabila Saifana; Dirvi Surya Abbas; Hamdani Hamdani; Basuki Basuki (BADAN PENERBIT STIEPARI PRESS, 2022)
The purpose of this study is to to examine the effect of company complexity, type of industry, client profitability, Company Size, and independent commissioners on audit fees. The population taken in this study are Manufacturing Companies listed on the Indonesia Stock Exchange in 2016-2021. The sample used is 39 companies and the total sample is 234. The data used is secondary data. The analytical method used in this study is panel data regression analysis using Eviews version 10 software. The complexity of the company has a significant effect on the Audit Fee. Type of Industry has a significant effect on Audit Fee. Client profitability has a significant effect on Audit Fee. Company size has a significant effect on Audit Fee. The Independent Commissioner has a significant effect on the Audit Fee.